PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII5 SMP NEGERI 25 PEKANBARU - Sipakkar, Susi Ermina; Roza, Yenita; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is based on the low students’math achievement of students in class VIII5 SMP Negeri 25 Pekanbaru. Based on daily test for Algebra lesson there are 18 of 40 students (45%) who achieved the Minimum Mastery Criteria is 75. The type of this research is classroom action research and the purpose of this research is to improve the learning process and increase students’math achievement by implementing cooperative learning model of type Think Pair Square. The subject of this research were students in class VIII5 SMP Negeri 25 Pekanbaru at the first semester of academic year 2015/2016. Students in this research are 40 people, there are 20 boys and 20 girls. The instruments of data collection in this research were observation sheets and mathematics achivement tests. The observation sheets were analyzed in narrative descriptive and mathematics achivement tests were analyzed in descriptive statistic. Based on analyzed showed that are : (1) the improvement of learning process after the implementation cooperative learning model of type Think Pair Square in mathematics in class VIII5 SMP Negeri 25 Pekanbaru by analyzed observation sheets; (2) increase the students’ math achievement with the percentage of students achieve Minimum Mastery Criteria in first cycle is 55% and in second cycle is 70%. The conclusion of this research is the implementation of cooperative learning model type Think Pair Square can improve the learning process and improve students’ math achievement at class VIII5 SMP Negeri 25 Pekanbaru of first semester of academic year for Relation and Function lesson.Key Word : Students’ math Achievement, Cooperative Learning Model type of Think Pair Square, Classroom Action Research.